Association of Diet Diversity and Pocket Money with Nutritional Status of High School Students - Marifah Nur Az-zahra Sulistyo; Arindah Nur Sartika (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Abstract: Adolescence could be a move between childhood and grown-up stages. The predominance of overweight adolescents remains high in Bekasi, a megapolitan city in Indonesia. Adolescents' overweight can be caused by undesirable ways of life such as destitute eating propensities. Moreover, young people receive money from their guardians to purchase high-calorie snacks. This considers points to dissect the relationship of diet diversity and pocket money with the wholesome status of students at SMA Patriot Bekasi. The study is categorized as a cross-sectional study. The inquiry about the test was comprised of 145 students from a private school in Bekasi named SMA Patriot. Data were gathered using a structured questionnaire, the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and Individual Dietary Diversity Score (IDDS). The measurable examination utilized was the chi-square test. According to the findings, two-thirds of those students had high pocket money and were overweight. With a substantial p-value of 0.001, the amount of pocket money and nutritional status were associated. However, there was no significant association between dietary diversity and nutritional status. In conclusion, there is an association between dietary diversity and pocket money with adolescents' nutritional status, and there is no significant association between diet diversity and nutritional status at SMA Patriot Bekasi. This study recommends holding health promotions about adolescent nutrition so the students can use their pocket money wisely to buy snacks during school.